Evaluation of the Sustainability Messages of the Companies with the Highest BIST Sustainability Index on X (Twitter) Platform - Vildan Gülpınar Demirci; Başak Buluz Kömeçoğlu (Hitit Sosyal Bilimler Dergisi)

(untitled)
BIST Sustainability Index was created to increase the understanding, knowledge, and practices on sustainability among Borsa Istanbul companies in Turkey. The BIST Sustainability Index aims to guide companies in the process of establishing policies regarding the environmental, social, and corporate governance risks of stock exchanges. In addition, it has the mission of creating a platform that communicates information on companies' sustainability policies to responsible investors. In line with the United Nations Sustainability Development Goals, several metrics are presented according to the sustainability practices of companies in Borsa Istanbul. Social networks are a tool that businesses frequently use to disseminate information quickly and at low cost. It has a key role in disseminating information about social marketing activities, especially in the sustainability axis. This study focuses on how companies use social networks to disseminate sustainability information. For this purpose, the sustainability messages of the 12 companies with the highest scores in the BIST sustainability index on the social network X platform for the years 2014-2022 are analyzed. The aim of the study is to examine whether there is a relationship between the companies' BIST sustainability index scores and the intensity of their use of sustainability messages on the social network. X platform data was obtained with the Python programming language, twint library. The correlation test was carried out using the SPSS package program with the Spearman Correlation test. As a result of the research, it is seen that the most frequently used keywords/phrase groups in the posts made by all companies are "education, energy, climate, women, health, water, sustainable, wages, production". The study did not find a significant relationship between the BIST sustainability index scores and the intensity of companies' messages containing sustainability keywords on the platform. This shows that companies should use social networks more efficiently in the dissemination of sustainability activities. Knowing how companies use social media to disseminate sustainability information can provide guidance for other companies. On the other hand, within the scope of the research, the messages of the companies were analyzed and the sustainability keywords were divided into three themes. The first theme is health, education, and women; the second theme is climate and environment; and the third theme is energy and savings. These themes and keywords are expected to serve as a source for content analysis studies such as social media messages and sustainability reports. Although no similar study has been found in Turkey, this study is one of the rare studies in the world literature. Unlike the literature, the sustainability activities on social media of the companies ranked at the top of the BIST Sustainability Index are analyzed. Thus, the activities carried out by companies that have already been determined to be successful in sustainability activities with a metric will serve as an example for companies that are not included in this list. On the other hand, the themes obtained from the research can be utilized in the dissemination of sustainability information on social media.